2015
DOI: 10.1021/acs.orglett.5b02835
|View full text |Cite
|
Sign up to set email alerts
|

Can Palladium Acetate Lose Its “Saltiness”? Catalytic Activities of the Impurities in Palladium Acetate

Abstract: Commercially available palladium acetate often contains two major impurities, whose presence can impact the overall catalytic efficacy. This systematic study provides a comparison of the differences in catalytic activity of pure palladium acetate, Pd3(OAc)6, with the two impurities: Pd3(OAc)5(NO2) and polymeric [Pd(OAc)2]n in a variety of cross-coupling reactions. The solid state (13)C NMR spectra of all three compounds in conjunction with DFT calculations confirm their reported geometries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 32 publications
1
50
1
1
Order By: Relevance
“…The trimeric structure of 1 in benzene or glacial acetic acid at room temperature, determined by osmometry, was first reported by Wilkinson and co‐workers . We also recently verified the trimeric structure in the solid state through 13 C NMR solid‐state spectroscopy in conjunction with DFT calculations (Figure ) . This is important as some suppliers incorrectly claim that palladium acetate is monomeric in nature.…”
Section: Structure–activity Studies Of Palladium Acetatesupporting
confidence: 70%
See 4 more Smart Citations
“…The trimeric structure of 1 in benzene or glacial acetic acid at room temperature, determined by osmometry, was first reported by Wilkinson and co‐workers . We also recently verified the trimeric structure in the solid state through 13 C NMR solid‐state spectroscopy in conjunction with DFT calculations (Figure ) . This is important as some suppliers incorrectly claim that palladium acetate is monomeric in nature.…”
Section: Structure–activity Studies Of Palladium Acetatesupporting
confidence: 70%
“…Cotton found that by using anhydrous solvent a single peak for 1 can be obtained by 1 H NMR spectroscopy . While we have found that sodium‐dried C 6 D 6 stored in a N 2 ‐filled glovebox works best to obtain a single peak for a pure sample of 1 ( δ =1.63 ppm in C 6 D 6 ), the use of CDCl 3 (stored over K 2 CO 3 ) is more practical in determining the amount of 2 present because of the higher resolution gained between 1 and 2 (Figure ) in the proton spectrum. Thus, using dried CDCl 3 and an internal standard (1,4‐dimethoxybenzene), we developed a simple method to quantitatively measure the concentration of 2 present in a commercial sample (Figure )…”
Section: Review On Synthesis Purity and Characterizationmentioning
confidence: 81%
See 3 more Smart Citations